Methodologies for the Characterization and Identification of Natural Atacamite as a Pigment in Andean Colonial Painting - de Haro, Andrea Mariel (2023)
Painting materials used in Spanish American Colonial art comprised pigments and binders from European origin as well as those that were already known in pre-Hispanic times. In recent years, we have identified for the first time the mineral atacamite, a basic copper chloride (Cu2Cl(OH)3), in Andean Colonial art pieces (Viceroyalty of Peru, 16th–18th centuries). This work proposes a methodology based on a multitechnical approach to identify and establish the origin (natural or synthetic) of the atacamite pigment in Andean cultural heritage objects. Optical microscopy (OM), scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS), portable X-ray fluorescence spectroscopy (pXRF), attenuated total reflection infrared spectroscopy (FTIR-ATR), micro-Raman spectroscopy, and wide-angle X-ray scattering (WAXS) were applied to analyse green pigments from the altarpiece of the Church of Ancoraimes, atacamite mineral samples from Chile, and atacamite obtained as a secondary product from traditional recipes used to produce verdigris, a copper acetate. Viride salsum by Teófilo Presbítero (SXII) and the Spanish translation by Andrés de Laguna (1566) of “De Materia Médica” from Dioscorides are both texts that include recipes involving the use of metallic copper as a starting material. These studies will contribute to the history of Spanish American Colonial art and to the knowledge on technological capacities and skills in the Andean region during this period.